Eksistensi Digital Evidence dalam Hukum Acara Perdata - Nurfauzah Maulidiyah; Yustria Novi Satriana (Jurnal Cakrawala Hukum, 2019)
Electronic Evidence Tools can be presented at the hearing as valid evidence and have been regulated separately in the ITE Law. However, in the Civil Procedure Law the formal legality has not been regulated how to show. Formulation of the problems raised in this writing (1) How is the legal certainty of the Electronic Evidence in the Civil Procedure Code; (2) What is the ideal arrangement regarding Electronic Evidence Tools in Civil Procedure Code; The first discussion is that Article 5 Paragraph (1) and (2) of Law No. 19 of 2016 concerning Information and Electronic Transactions (UU ITE) which only provides legal certainty to the extent of the recognition of the existence of Electronic Evidence Tools as valid evidence. There must be an ideal arrangement regarding the Electronic Evidence Tool in the Civil Procedure Code to ensure the legal certainty of the procedure for submission and enforcement is: first, with a mechanism for renewing the HIR and RBg. Second, the party that has the authority to stipulate a Circular of the Supreme Court on how the parties know and see the Electronic Evidence Tool and the procedure for submitting Electronic Evidence Tools.